A Hybrid Self‐Powered Arbitrary Wave Motion Sensing System for Real‐Time Wireless Marine Environment Monitoring Application. Issue 7 (21st December 2021) - Bhatta, Trilochan; Maharjan, Pukar; Shrestha, Kumar; Lee, Sanghyun; Salauddin, Md.; Rahman, M. Toyabur; Rana, S. M. Sohel; Sharma, Sudeep; Park, Chani; Yoon, Sang Hyuk; Park, Jae Yeong
Abstract: Self‐powered arbitrary wave monitoring is a hot research topic which aims to remove of the trouble associated with managing conventional power for continuous and real‐time acquisition of wave information from the marine environment. Herein, an effective approach is presented that simultaneously generates power from arbitrary motion waves and can sense and wirelessly transmit the wave information without requiring an external supply. The hybridized ellipsoidal device inspired from an elliptical trajectory of objects over shallow water waves, consists of six planar spiral coils arranged to cover the arbitrary direction of waves for power generation. Four magnetic force‐actuated triboelectric nanogenerators (TENGs) pairs along four sides as the arbitrary direction self‐powered wave motion sensors are integrated. Furthermore, all the required circuitry for signal processing and wireless transmission are integrally powered by the generated electricity to realize a self‐sustained wireless marine environment monitoring system. The generator can deliver peak power of 106  and 44.8 mW (at 3Hz) along with major and minor axis motion directions. The self‐powered sensors have excellent motion sensitivity thus the signals obtained from these sensors are utilized to acquire useful information related to the water waves which are very crucial parameters for real‐time monitoring of the marine environment. Abstract : A self‐sustained arbitrary wave motion sensing system is developed by integrating magnetic force actuated triboelectric‐based self‐powered motion sensors and electromagnetic‐based generators. The integrated device enables self‐powered detection of various wave parameters with sufficient accuracy and sensitivity. With the harvested energy, it is possible to transmit wave information wirelessly to a smartphone for future marine applications.